On the Front Lines: A Primary Source for the Analysis of a German Trooper’s Daily Experiences from 1914–1916 (KULT_online, 2013)
Evelyn Hemmerich’s monograph Heute nach vorn. Alltag und Erlebnis des August Stark aus Nassau-Scheuern im Ersten Weltkrieg (Today Forward: The Everyday Life and Experience of August Stark from Nassau-Scheuern in World War I) consists of two different parts. The first part covers August Stark’s daily routine and experiences as a trooper in World War I, during which he fought on various fronts. The second part is a transcription of the main documents that underlie the historical research. Particularly significant here is the fact that August Stark was deployed to numerous sites and battlegrounds, and therefore the published material provides a valuable insight into a soldier’s way of life during World War I. It is of astonishing quality, and thus well suited for subsequent research projects on this topic.